Using formative process evaluation to improve program implementation and accessibility of competitive group-based physical activity in the TEAM-PA trial - Allison M. Sweeney; Dawn K. Wilson; Nicole Zarrett; Timothy Simmons; Makayla Mansfield; Lindsay Decker (BMC, 2024)
Abstract Background This study demonstrates how formative process evaluation was used to assess implementation and improve dose and fidelity in the Together Everyone Achieves More Physical Activity (TEAM-PA) randomized controlled trial. TEAM-PA uses a randomized group cohort design to evaluate the efficacy of a group-based intervention for increasing physical activity among African American women. Methods Intervention groups met for 10 weeks and were co-led by female African American facilitators, with intervention sessions consisting of group feedback, a health curriculum, group-based physical activity games, and group-based goal-setting. Drawing from a multi-theoretical framework, the intervention targeted social affiliation using collaborative and competitive group strategies, including essential elements focused on group-based behavioral skills, peer-to-peer positive communication, collectivism, optimal challenge, social facilitation, and peer to peer challenges. Formative process evaluation was used to monitor reach, dose, and fidelity, and implement feedback and solutions. Results Across two cohorts, four groups (n = 54) were randomized to the TEAM-PA intervention. On average 84.8% of participants attended each week, which exceeded the a priori criteria. Results from the systematic observations indicated that on average 93% of the dose items were completed in each session and adequate levels of fidelity were achieved at both the facilitator and group-levels. Participants were compliant with wearing the FitBits (6.73 ± 0.42 days/week) and most participants successfully contributed to meeting the group-based goals. The use of open-ended items also revealed the need for additional modifications to the group-based PA games, including allowing for individuals to take breaks, incorporating a broader range of exercises, minimizing activities that required bending/reaching down without assistance, and providing facilitators with additional training for implementing the games. Initial evidence suggests that these changes were successful in increasing participants' comprehension of the games from Cohort 1 (M = 1.83, SD = 0.71) to Cohort 2 (M = 3.33, SD = 0.69). Conclusion Findings from this study demonstrated high levels of reach, dose, and fidelity, while also highlighting strategies for implementing competitive group-based PA games that are accessible across physical fitness levels. Formative process evaluation, including open-ended items and collaborative brainstorming, holds tremendous potential for improving future interventions. Trial registration This study was registered on Clinicaltrials.gov (# NCT05519696) on August 22, 2022 prior to the enrollment of the first participant on September 12, 2022 ( https://clinicaltrials.gov/study/NCT05519696?term=NCT05519696&rank=1 ).